A full factorial design study used to improve the extraction of cannabinoids from CBD-dominant cannabis flower using subcritical-CO₂ extraction - Collett, Cayla (Kansas State University, 2023)
Subcritical carbon dioxide (sub-CO₂) extraction of cannabinoids can be optimized by understanding the parameters that significantly affect the extraction process. Extraction parameters, such as temperature, pressure, and extraction time, have been shown in multiple studies to affect the extraction process greatly. However, the effects of variabilities in the starting biomass are not often considered. To study the effect these variables have on the extraction process, a design of experiments approach was used to analyze prerecorded data from a cannabis oil production plant. A two-level, full factorial design with two variable components over eight batches was analyzed for process improvement. The factors considered include the initial total cannabidiol (CBD) content and initial moisture content, which was varied with a decarboxylating drying process prior to extraction. The effects of extraction time were also considered by individually analyzing the mass percent yield separated after 2, 4, and 6 hours for each trial. The statistical analysis determined that all variables considered, extraction time, the total CBD content, and a decarboxylating drying pretreatment (moisture content), had statistically significant effects on the mass percent yield of sub-CO₂ cannabis extract produced. These findings suggest that a decarboxylating drying process implemented before extraction would significantly increase the extraction efficiency by increasing the mass percent yield of CBD-dominant cannabis extract separated when using sub-CO₂ extraction.
Keywords: Subcritical extraction; Cannabidiol